Adding insult to injury: Illegitimate stressors and their association with situational well-being, social self-esteem, and desire for revenge. Issue 3 (3rd July 2021) - Semmer, Norbert K.; Jacobshagen, Nicola; Keller, Anita C.; Meier, Laurenz L.
ABSTRACT: Implying an offense to self, appraising a stressor as indicating a lack of consideration by others should have effects beyond its stressfulness per se. In Stress-as-Offense-to-Self theory (SOS), such stressors are called "illegitimate stressors." We assessed situations appraised as stressful in two diary studies ( N1 = 117, N2 = 137). Outcome variables were feelings of resentment in both studies, plus nervousness, anxiety, and sadness in Study 1 and depressive mood, threat to social self-esteem, and desire for revenge in Study 2. Controlling for stressfulness, perceived illegitimacy predicted affective reactions that are outward-directed (feelings of resentment [Studies 1 and 2], threat to social self-esteem and desire for revenge [Study 2]); it also predicted sadness in Study 1 but not depressive mood in Study 2, nor nervousness (Study 1). Thus, not all hypotheses were confirmed but the pattern was as expected, in that results were consistent regarding outcomes typically associated with the attribution of blame. The independent contribution of perceived illegitimacy aligns well with the underlying Stress-as-Offense-to-Self theory. Practical implications refer to efforts to avoid illegitimate stressors, for instance by perspective-taking, by showing appreciation and support, and by supporting such behaviours through keeping stressors in general at a manageable level.